Lower extremity muscle morphology in young athletes: An MRI-based analysis - Tate, C. M.; Williams, G. N.; Barrance, P. J.; Buchanan, T. S. (Medicine & Science in Sports & Exercise, 2006)
Purpose: This study was conducted to describe lower extremity muscle morphology (volume and peak cross-sectional area (CSA)) in young athletes and compare these with previously reported values. A second aim was to determine if muscle morphological values differ significantly between sides, implying that unilateral measurements cannot represent both limbs accurately.